The psychological impact of a diagnosis of Alzheimer's disease. (May 2014) - Lee, Suzanne M; Roen, Katrina; Thornton, Amanda
Research on the experience of receiving and living with a diagnosis of dementia is sparse. Existing studies have focused on the initial reactions to the diagnosis rather than longer term adjustment and coping. The current study uses interpretative phenomenological analysis to explore personal experiences of receiving a diagnosis and to investigate aspects of the experience of adjusting and adapting to dementia. This is a cross-sectional study drawing on semi-structured interviews with 10 participants who had a diagnosis of mild Alzheimer's disease. The findings illustrated the importance, to people with Alzheimer's disease, of understanding and making sense of the diagnosis to help them deal with issues of loss and to make positive adjustments to their lives through employing specific coping strategies. The findings also appeared to challenge misconceptions held by some professionals in relation to possible negative effects of disclosing a diagnosis of dementia.